1996
DOI: 10.1111/j.1095-8649.1996.tb06084.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of macrourids in the upper slope of the north‐western Ionian Sea

Abstract: Aspects of reproduction of macrourid fish in the north‐western Ionian Sea are reported. Data were collected during 12 trawl surveys carried out between 1993 and 1995. Mature and running ripe females of Coelorhynchus coelorhynchus, Hymenocephalus italiens and Nezumia sclerorhynchus were found all year round. Mature females of Trachyrhynchus trachyrhynchus were found mainly in August.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In C. coelorhynchus reproduction was assumed to be between November and May by Sardou (1970) and during spring-summer by Massuti et al (1995). D'Onghia et al (1996), investigating a wider area in the Ionian Sea, found small numbers of ripe specimens of C , coelorhynchus throughout the year with little increase from autumn to spring.…”
Section: Discussionmentioning
confidence: 99%
“…In C. coelorhynchus reproduction was assumed to be between November and May by Sardou (1970) and during spring-summer by Massuti et al (1995). D'Onghia et al (1996), investigating a wider area in the Ionian Sea, found small numbers of ripe specimens of C , coelorhynchus throughout the year with little increase from autumn to spring.…”
Section: Discussionmentioning
confidence: 99%
“…Overall macrourids are known to have adapted to various ranges of food availability by employing generalist and opportunistic foraging strategies (Pearcy and Ambler 1974, Macpherson 1979, Mauchline and Gordon 1984. In addition, they can have a continuous spawning span in the Mediterranean Sea (Massutí et al 1995, D'Onghia et al 1996, 1999, Fernandez-Arcaya et al 2013) and can be found in habitats less impacted by fishing activities, such as submarine canyons and cold-water coral communities, which can act as shelters from trawling (Tursi et al 2004;D'Onghia et al 2010, Fernandez-Arcaya et al 2013. Most macrourid species find refuge in deep waters since they exceed the depth range sought by fishing in the Mediterranean (D'Onghia et al 2004a, b, Follesa et al 2011, Tecchio et al 2013.…”
Section: Time-related Trendsmentioning
confidence: 99%
“…The bigeye grenadier are known to occur occasionally in the diet of D. eleginoides in the waters around South Georgia and Macquarie Island (Goldsworthy et al ., 2001) and may be an important prey item for deep diving vertebrate predators such as the elephant seal Mirounga leonina . Although studies have been conducted on aspects of the ecology of a range of macrourid species (D’Onghia et al ., 1996; Kelly et al ., 1996), information for M. holotrachys is scarce. The purpose of the present study was to collect new data on the biology of M. holotrachys caught as by‐catch in the long‐line fishery for Patagonian toothfish from CCAMLR sub‐area 48·3 (South Georgia and Shag Rocks) to assist with the provision of management advice for the species at South Georgia.…”
Section: Introductionmentioning
confidence: 99%